PERSEPSI MAHASISWA TERHADAP AKUN INSTAGRAM @INFOUNP SEBAGAI MEDIA INFORMASI AKADEMIK - Muhammad Fadly; Desriyeni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the perceptions of students of the Department ofInformation and Library Science, Padang State University, towards the Instagramaccount @infounp as an academic information medium. This study uses aquantitative approach with a descriptive method. The data collection techniquewas carried out by distributing online questionnaires to 78 active students who arefollowers of the @infounp account, with the sample determined using the Slovinformula. The research instrument was compiled based on five indicators of theUses and Gratifications theory, namely: information needs, timeliness, clarity ofinformation, ease of access, and user satisfaction. The results showed thatstudents perceptions of the @infounp Instagram account were generally in thevery good category with an achievement score of 82.0%. From the analysis, thefindings of the average score for each indicator were as follows: information needs(4.08), timeliness (3.97), clarity of information (4.17), ease of access (4.08), anduser satisfaction (4.08). These findings indicate that the @infounp account hasplayed an effective role in conveying academic information to students, althoughthere are still notes regarding the clarity and interactivity in delivering its content.